Silver Nanoparticle Production by Ruta graveolens and Testing Its Safety, Bioactivity, Immune Modulation, Anticancer, and Insecticidal Potentials - Hamed A. Ghramh; Essam H. Ibrahim; Mona Kilnay; Zubair Ahmad; Sadeq K. Alhag; Khalid Ali Khan; Ramadan Taha; Fawziah M. Asiri (Bioinorganic Chemistry and Applications)
Ruta graveolens, a plant belonging to the family Rutaceae, is traditionally used as a medicinal plant and a flavoring agent in food. This work aimed to prepare silver nanoparticles (AgNPs) using the ethanol extract from R. graveolens leaves and test different biological activities as well as insecticidal potentials in the extract and extract prepared AgNPs. Dried and powdered R. graveolens leaves were subjected to extraction using ethanol, and this extract was used to synthesize AgNPs. AgNP synthesis was monitored by the change in color, UV spectrophotometry, and electron microscopy (scanning). Fourier transform infrared (FT-IR) spectroscopy was used to monitor the functional groups in the extracts. Immunological, physiological, anticancer, antibacterial, and insecticidal potentials of the extract and its prepared AgNPs were tested. Results showed the ability of the leaf extract to synthesize. SEM examination revealed a spherical shape of AgNPs with a size of 40–45 nm. The extract contained many functional groups as indicated by FT-IR. The extract alone inhibited the growth of normal rat splenic cells, while the extract containing AgNPs stimulated its growth. Extract alone stimulated HeLa cell proliferation and inhibited HepG2 growth, while both cell line growth was inhibited by the extract containing AgNPs. Both the extract and extract with AgNPs were safe on RBCs and did not cause any severe elevation in liver enzymes. The extract alone and with AgNPs showed insecticidal activity against Culex pipiens. Our findings suggest that the R. graveolens leaf extract, alone or with AgNPs, is biologically safe on animal cells and has antibacterial, insecticidal, and immunomodulation potentials.